On DABAL-Me₃ promoted formation of amides - Dubois, Nathalie; Glynn, Daniel; Mcinally, Thomas; Rhodes, Barrie; Woodward, Simon; Irvine, Derek; Dodds, Chris (Elsevier, 2013)
The range and utility of DABAL-Me3 couplings of methyl esters and free carboxylic acids with primary and secondary amines under a variety of conditions (reflux, sealed tube, microwave) has been compared for a significant range of coupling partners of relevance to the preparation of amides of interest in pharmaceutical chemistry. Commercial microwave reactors promote the fastest couplings and allow the use of significantly sterically hindered amines (primary and secondary) and carboxylic acids derivatives. The influence of microwave energy on the reaction system was shown to be typically related to thermal effects (over-pressuring and superheating).